Communicating by electrolarynx with a blind tetraplegic spinal cord injury patient on mechanical ventilation in the ICU - Shimizu, K; Ogura, H; Irisawa, T; Nakagawa, Y; Kuwagata, Y; Shimazu, T (Spinal cord, 2013)
Study design: Single-subject case. Objectives: To describe the atypical presentation of communication with a blind tetraplegic spinal cord injury patient on a respirator using an electrolarynx. Setting: Critical care center in Osaka, Japan. Methods: A 53-year-old blind man with tetraplegic spinal cord injury was admitted to our center. It was difficult for him to express his desires and to communicate with others about his severe condition and other details of his care. We began to use an electrolarynx to communicate with this patient because he could move his mouth. Results: With use of the electrolarynx, the patient gradually became better able to speak fluently by electrolarynx on the first day of use. The electrolarynx allowed us and his family to communicate with him. He was pleased with the improvement in communication. Conclusion: An electrolarynx is a useful method for communicating with blind tetraplegic spinal cord injury patients on mechanical ventilation.